Looney tunes platinum collection. Volume 3 [videorecording (DVD)] ([Publisher not identified], 2012)
Make way for Looney Tunes Platinum Collection Volume 3 with over five hours of insightful documentaries, additional rare shorts, featurettes, commentaries and more. Selections include the core characters, such as Bugs Bunny, Daffy Duck, Porky Pig, Tweety and Sylvester, Pepe Le Pew and Foghorn Leghorn.